A Study of Students Data Base Followed up for Five Years in The New School of Medicine in Ndola, Zambia. - Mugala, Duncan D (Advances in Social Sciences Research Journal, 2017)
The School of Medicine on the Copper belt was started in October 20 11. We selected the best of the best students from CBU, the best of all students who did a two year study of A Levels in Zambia or abroad, the best Diploma holders of those who did a dental course done in Lusaka and indeed all who were degree holders of a science who had the best grades. Our students had to pass through the school of medicine for a period of five years in which they had tests, assignments and ends of terms and years examinations. After five years in the School of Medicine at the Ndola Teaching Hospital ; the first students graduated on 29th September 2016. When our medical students joined the school of Medicine, they were exposed widely: Global health issues were encouraged as early as students entered medicine, some students published health publications worldly, they practiced medicine among the poor of Chipulukusu compound of Ndola and sometimes handled ethnic minorities in Ndola . In addition, some medical students travelled out of Zambia due to an international clinical rotation and often reported a greater ability to recognize disease presentations. The whole aim is that our field of teaching, the education and research Medicine at the Ndola Teaching Hospital, will become really wide, thus our desires are to expose out teacher experience[7].